2016
DOI: 10.5935/1678-9741.20160063
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Tetralogy of Fallot in Adults: Early Outcomes

Abstract: ObjectiveTo study the in-hospital outcome of adult patients who had undergone surgical repair for Tetralogy of Fallot.MethodsA retrospective descriptive study was conducted at the Punjab Institute of Cardiology searching the hospital records. All those adult patients who had undergone repair for Tetralogy of Fallot from January 2012 to December 2014 were included in the study. All the patients were operated by the same surgical team. Patients who underwent primary repair as well as those with previous palliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 18 publications
(17 reference statements)
3
17
7
1
Order By: Relevance
“…9 Khan et al reported 8.0% mortality rate in late TOF patients. 13 In our study, the operative mortality was only 1.3% which was very low as compared to these studies. Wu et al reported the results of 212 patients who underwent TOF repair having age 1.5 year to 37 years.…”
Section: Discussioncontrasting
confidence: 61%
“…9 Khan et al reported 8.0% mortality rate in late TOF patients. 13 In our study, the operative mortality was only 1.3% which was very low as compared to these studies. Wu et al reported the results of 212 patients who underwent TOF repair having age 1.5 year to 37 years.…”
Section: Discussioncontrasting
confidence: 61%
“…In our series, 8 of 62 (12.9%) patients died during the perioperative period. This is higher than reported in many studies from the developed world, which report on younger patient populations and have more advanced perioperative facilities. As a surgical intervention for CHDs including TOF is not readily available in most sub‐Saharan countries, few studies exist against which we can compare our results.…”
Section: Discussioncontrasting
confidence: 56%
“…For instance, transannular patches are required more often in children than in adults, due to the more favorable anatomy encountered in adulthood [2] . In table 1, Khan et al [1] also showed a significant influence of age on the frequency in both right ventricular outflow tract and transannular patches.…”
mentioning
confidence: 90%
“…Khan et al. [1] reported 25% of moderate/severe postoperative pulmonary regurgitation in their study. In this context, how did they evaluate these patients?…”
mentioning
confidence: 93%
See 1 more Smart Citation